Current research in development of polycaprolactone filament for 3D bioprinting: a review. Issue 1 (November 2021) - Amni, C; Marwan,; Aprilia, S; Indarti, E
Abstract: Three-dimensional printing (3DP) provides a fast and easy fabrication process without demanding post-processing. 3D-bioprinting is a special class in 3DP. Bio-printing is the process of accurately 3DP structural design using filament. 3D bio-printing technology is still in the development stage, its application in various engineering continues to increase, such as in tissue engineering. As a forming material in 3D printing, many types of commercial filaments have been developed. Filaments can be produced from either natural or synthetic biomaterials alone, or a combination of the two as a hybrid material. The ideal filament must have precise mechanical, rheological and biological properties. Polycaprolactone (PCL) is specifically developed and optimized for bio-printing of 3D structures. PCL is a strategy in 3D printing to better control interconnectivity and porosity spatially. Structural stability and less sensitive properties environmental conditions, such as temperature, humidity, etc make PCL as an ideal material for the FDM fabrication process. In this review, we provide an in-depth discussion of current research on PCL as a filament currently used for 3D bio-printing and outline some future perspectives in their further development.